NO SIGNIFICANT CHANGES IN ADULT T-CELL LEUKEMIA VIRUS INFECTION IN OKINAWA AFTER INTERVALS OF 13 AND 15 YEARS - IKEMATSU, Hideyuki; KASHIWAGI, Seizaburo; KAJIYAMA, Wataru; HAYASHI, Jun; NOMURA, Hideyuki (Japanese Journal of Cancer Research GANN, 1986)
Two separate studies were carried out between 1968 and 1984; a total of 2, 021 serum samples from healthy subjects were collected in two districts of Okinawa-on Iriomote Island and in Ishigaki City. The first samples were collected in 1970 on Iriomote Island and in 1968 in Ishigaki City. The second samples were collected after an interval of 13 years in Ishigaki City and after an interval of 15 years on Iriomote Island. These serum samples were tested for the presence of antibody to adult T-cell leukemiaassociated antigen (anti-ATLA). The overall prevalence of anti-ATLA in both areas combined was 9.9% from 1968 to 1970 and that from 1981 to 1984 was 8.9%. At both times, anti-ATLA prevalence increased with age and was higher in females than in males. No significant changes in anti-ATLA prevalence was observed: after intervals of 13 and 15 years, the prevalence decreased from 10.2 to 9.9% in Ishigaki City and from 9.4 to 8.2% on Iriomote Island. These data suggest that there has been no significant change in the rate of infection with adult T-cell leukemia virus in recent years in the areas studied.